(untitled) (Lapai Journal of Economics, 2023)
This study evaluated the performance of residential property investments in Minna, Niger State, Nigeria. Data for the study were collected through field survey from estate surveying and valuation firms which are active in the residential property market in Minna. Thus, a total of 382 residential investment properties were selected from the property portfolio of estate surveying and valuation firms in the city for the study. Variables utilised for the study include the capital value, annual expenses in form of taxes, rates, repairs etc. and annual rental value of 1-BR, 2-BR and 3-BR apartments for the period, 2009 – 2021 and analysed using analysis of variance, geometric mean and coefficient of variation. The findings indicate that the variance in total return for all residential investment property types across all the study locations is statistically significant, also the risk associated with this return varies according to the residential property investment types across all the locations considered in the study. The study recommends that prudent residential real estate investors in the city require impeccable pre-investment appraisal of residential property investments at all locations in the city before investing their capital, particularly if they are risk averse.